Increasing Motivation and Interest in Learning Through SISIPJA's interactive digital media - Rezkia, Dicha Putri; Gimin, Gimin; Gusnardi, Gusnardi; Suarman, Suarman; Riadi, R.M (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This research aims to develop an interactive digital learning media, SISIPJA (Accounting Cycle for Service Companies), to enhance students' motivation and interest in learning. The research method employed is Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjectsinvolved 114 students of SMK Negeri 4 Pekanbaru. Data were collected through interviews and questionnaires, and were analyzed using descriptive statistics, t-tests, and n-gain analysis to measure the effectiveness. The results of media validation based on the assessment of 1 media expert and 2 material experts indicate that the SISIPJA media is highly suitable for use, with a final validity score categorized as very suitable, along with several suggested improvements. At the implementation stage, the SISIPJA media was applied in accounting learning and resulted in a significant increase in students' motivation and interest in learning, with a medium n-gain category. This means that the interactive digital learning media SISIPJA is considered very positive and suitable for use in accounting learning.